Economic and heating efficiency analysis of double-shell downhole electric heater for tar-rich coal in-situ conversion. (January 2023) - Wang, Zhendong; Yang, Fu; Fu, Deliang; Ma, Li; Duan, Zhonghui; Wang, Qiuwang; Kang, Shijie; Guo, Wei
Abstract: Downhole electric heater studied in this paper is used for tar-rich coal in-situ conversion, and the closed double-shell structure is proposed to improve the performance and economy of heater. In this paper, four downhole electric heaters were experimentally studied, and the single-shell heater was used as the control. According to the experimental results, it can be seen that the mass flow rate has a great impact on the total cost, and the parallel double-shell downhole electric heater has the highest total cost. In addition, the larger the helical pitch or the heater shell diameter, the lower the heater shell surface temperature, and thermal radiant is the main way of heater shell to lose heat, which is accounts for 78.91%–92.91%. Moreover, from the perspective of heat transfer quality, heater with closed double-shell structure is more efficient than the single-shell heater, and the energy utilization efficiency of heater with closed double-shell structure achieves 97.38%–99.59%. Finally, taking the comprehensive cost of in-situ exploitation of tar-rich coal into account, the small outer shell diameter is an optimal choice for the heater with closed double-shell structure.